Nanococrystals in Pharmaceutical Development: Design, Characterization, and Applications - Sharon Susanto (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Drug solubility is a fundamental challenge in pharmaceutical development, especially for oral dosage forms where poor solubility limits therapeutic effectiveness. Among the approaches explored to address this issue, cocrystals and nanocrystals have shown notable advantages in improving physicochemical properties and drug delivery. Nanococrystals, which integrate the principles of both systems, represent a promising platform with potential benefits in solubility, bioavailability, and stability. This study was designed as a systematic literature review of publications from 2015 to 2025 retrieved from PubMed, Scopus, Web of Science, and ScienceDirect. Relevant studies were analyzed thematically to provide insights into nanococrystal design, including the role of active pharmaceutical ingredients, coformers, stabilizers, and solvents. Fabrication methods such as antisolvent precipitation, wet milling, high pressure homogenization, and spray flash evaporation were reviewed alongside characterization techniques including X-ray diffraction, thermal analysis, spectroscopy, and microscopy. Applications of nanococrystals consistently demonstrate significant improvements in solubility, dissolution rate, and oral bioavailability compared to conventional forms, confirming their potential as an advanced drug delivery strategy for future pharmaceutical development.